1993
DOI: 10.1007/bf00216448
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of factor VII deficiency in Italy: a frequent mutation (FVII Lazio) in a repeated intronic region

Abstract: Molecular defects and polymorphic haplotypes of coagulation factor VII gene were studied in eight unrelated Italian subjects with factor VII deficiency, seven having the factor VII- variant, one the factor VIIR variant. An intron 7 mutation, which alters the consensus donor splice site sequence, was found in six subjects. The presence of the founder effect is suggested by their common geographical origin (a mountain area in the Lazio region) and by the identical polymorphic haplotype underlying the mutation. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 25 publications
0
43
0
Order By: Relevance
“…As a model to exploit snRNAs for restoration of correct splicing in coagulation factor deficiencies, we chose the 9726 ϩ 5g/a mutation 17 in FVII occurring in the donor splice site of intron 7 (IVS7) at the ϩ 5 position, whose substitution has been frequently found to be associated with human diseases. [7][8][9] The homozygous patients experienced life-threatening hemorrhagic symptoms and require replacement therapy.…”
Section: Introductionmentioning
confidence: 99%
“…As a model to exploit snRNAs for restoration of correct splicing in coagulation factor deficiencies, we chose the 9726 ϩ 5g/a mutation 17 in FVII occurring in the donor splice site of intron 7 (IVS7) at the ϩ 5 position, whose substitution has been frequently found to be associated with human diseases. [7][8][9] The homozygous patients experienced life-threatening hemorrhagic symptoms and require replacement therapy.…”
Section: Introductionmentioning
confidence: 99%
“…A point mutation (9726ϩ5GϾA, FVII Lazio) affecting nucleotide ϩ5 of intron 7, which is part of the splicing consensus sequence, has been identified as a common cause of CRM Ϫ FVII deficiency in central Italy. 16 FVII Lazio homozygous individuals have undetectable FVII levels and are usually severe bleeders. 16 In vitro expression experiments have shown that the FVII Lazio mutation activates a cryptic splice site in the second minisatellite repeat, leading to a 37-nucleotide insertion in the mature transcript, which in turn causes a frameshift and premature termination of translation.…”
Section: Introductionmentioning
confidence: 99%
“…16 FVII Lazio homozygous individuals have undetectable FVII levels and are usually severe bleeders. 16 In vitro expression experiments have shown that the FVII Lazio mutation activates a cryptic splice site in the second minisatellite repeat, leading to a 37-nucleotide insertion in the mature transcript, which in turn causes a frameshift and premature termination of translation. Only 0.2% to 1% of all FVII Lazio mRNA is spliced correctly, resulting in a very small amount of normal FVII.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 Mutagenesis and transfection expression vectors were created by site-directed mutagenesis of plasmid pCDNA3-FVII. 13 Oligonucleotides for mutagenesis spanned the following complementary DNA nucleotides: (1) 1193 through 1220 containing the 1206G Ͼ A transition (Gly331Ser) or the 1207G Ͼ C transversion (Gly331Ala); (2) 1040 through 1073 containing the 1062G Ͼ A transition (Gly283Ser) or the 1063 G Ͼ C transversion (Gly283Ala).…”
Section: Genetic Analysismentioning
confidence: 99%